Combined transjugular/percutaneous intrahepatic portosystemic shunts (cTIPS) for cavernous transformation of the portal vein after conventional transjugular approach TIPS failure. Issue 16 (21st April 2023) - Bi, Yonghua; Ren, Jianzhuang; Han, Xinwei; Guo, Kefeng; Tu, Xueliang
Abstract : This study aim was to compare the safety and efficacy of combined transjugular/percutaneous intrahepatic portosystemic shunts (cTIPS) and transjugular intrahepatic portosystemic shunt (TIPS) in cirrhotic patients with cavernous transformation of the portal vein (CTPV) after conventional transjugular approach TIPS failure. Cirrhotic patients who were diagnosed as CTPV and treated by cTIPS or TIPS between July 2012 and April 2022 were retrospectively analyzed. Patients' characteristics and clinical data were recorded. The clinical outcomes, long-term survival rates and patency rates between the 2 groups were compared. A total of 68 patients with CTPV were enrolled, of whom 23 were treated with TIPS and 45 with cTIPS. The initial technical success was 30.9% in TIPS group and 91.1% in cTIPS group. The hospitalization days increased significantly in the cTIPS group compared with TIPS group ( P = .0131). However, the complication rate, patency rates and survival rates were similar between the 2 groups. In conclusion, cTIPS appeared to be safe and effective in cirrhotic patients with CTPV after conventional transjugular approach TIPS failure.